Liraglutide 3.0 mg for the management of insufficient weight loss or excessive weight regain post‐bariatric surgery - Wharton, Sean (Clin Obes, 2019)
To assess the effectiveness of liraglutide 3.0 mg in post‐bariatric surgery patients, and to determine whether this would differ based on the type of bariatric surgery. One hundred seventeen post‐bariatric surgery patients from the Wharton Medical Clinic were analysed. Changes in weight while taking liraglutide 3.0 mg were examined for all patients, and by three types of bariatric surgery—Roux‐en‐Y gastric bypass, gastric banding and gastric sleeve. Patients primarily underwent Roux‐en‐Y gastric bypass (n = 53, 45.3%) or gastric banding (n = 50, 42.7%). Over 7.6 ± 7.1 months taking liraglutide 3.0 mg, patients lost a statistically significant amount of weight (−6.3 ± 7.7 kg, P < .05) regardless of the type of surgery they had (P > .05). This decrease in weight remained significant after 1‐year of taking liraglutide 3.0 mg (P < .05). Nausea was the most prevalent side effect, reported by 29.1% patients. While options for excess weight management in post‐bariatric surgery patients are limited, results of this study suggest that post‐bariatric surgery patients can lose a significant amount of weight while taking liraglutide 3.0 mg regardless of the type of surgery they had. Further, similar to non‐surgical populations, post‐bariatric surgery patients taking liraglutide 3.0 mg may experience gastrointestinal side effects such as nausea and can continue to lose weight up to 1 year.